(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: This Paper Compares Two Characters In Two Of The Most Intriguing Southern Novels Portraying The Southern Way Of Life. William Faulkner’s Absalom Absalom! And Margaret Mitchel’s Gone With The Wind Depict Two Characters, Thomas Sutpen And Gerald O’Hara Who Both Not Only Came From A Humble Background And Arrived In The South, But Also Accomplished Their American Dream(S)/Designs Representing The Southern Man, And The Collapse Of The Myth Of The South. The Paper Draws On The Comparison Of The Two Characters Accomplishing Their Plans And The Collapse They Endured From The Civil War, As The South Broke Down. Keywords: The South; Thomas Sutpen; Gerald O’Hara; Southerner; The Design; The American Dream.